2018
DOI: 10.1007/s00018-018-2799-7
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucose ceramide glucosyltransferase activates AKT, promoted proliferation, and doxorubicin resistance in breast cancer cells

Abstract: The UDP-glucose ceramide glucosyltransferase (UGCG) is a key enzyme in the synthesis of glycosylated sphingolipids, since this enzyme generates the precursor for all complex glycosphingolipids (GSL), the GlcCer. The UGCG has been associated with several cancer-related processes such as maintaining cancer stem cell properties or multidrug resistance induction. The precise mechanisms underlying these processes are unknown. Here, we investigated the molecular mechanisms occurring after UGCG overexpression in brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 53 publications
8
60
0
Order By: Relevance
“… 6 7 61 We annotated the fusobacterial MAGs and observed that while they did not contain key genes involved in TMA production (TMA-lyase ( cutC , K20038), and L-carnitine/gamma-butyrobetaine antiporter ( caiT , K05245)), several orthologues such as proline iminopeptidase (K01259), glutamate formiminotransferase (K00603) and tryptophanase (K01667) were prevalent in genomes from the Fusobacterium clade ( online supplementary table S12 ). Moreover, Fusobacterium clade genomes possess genes that may be involved in the catabolism of amino acids and production of glucose (phosphoenolpyruvate carboxykinase K01610, fructose-bisphosphate aldolase K01623, oxaloacetate decarboxylase K01571), as well as several other features that could be linked to cancer such as iron scavenging (K07230, K07243, K11707, K11708, K11709, K11710), 62 ceramide glucosyltransferase (K00720) involved in production of glycosylated sphingolipids 63 and para-aminobenzoate synthetase (K01664, K01665) in the production of folate. 64 Likewise, urease (K01428–K01430) 65 was detected in Fusobacterium_A and Fusobacterium_B clades but not Fusobacterium .…”
Section: Resultsmentioning
confidence: 99%
“… 6 7 61 We annotated the fusobacterial MAGs and observed that while they did not contain key genes involved in TMA production (TMA-lyase ( cutC , K20038), and L-carnitine/gamma-butyrobetaine antiporter ( caiT , K05245)), several orthologues such as proline iminopeptidase (K01259), glutamate formiminotransferase (K00603) and tryptophanase (K01667) were prevalent in genomes from the Fusobacterium clade ( online supplementary table S12 ). Moreover, Fusobacterium clade genomes possess genes that may be involved in the catabolism of amino acids and production of glucose (phosphoenolpyruvate carboxykinase K01610, fructose-bisphosphate aldolase K01623, oxaloacetate decarboxylase K01571), as well as several other features that could be linked to cancer such as iron scavenging (K07230, K07243, K11707, K11708, K11709, K11710), 62 ceramide glucosyltransferase (K00720) involved in production of glycosylated sphingolipids 63 and para-aminobenzoate synthetase (K01664, K01665) in the production of folate. 64 Likewise, urease (K01428–K01430) 65 was detected in Fusobacterium_A and Fusobacterium_B clades but not Fusobacterium .…”
Section: Resultsmentioning
confidence: 99%
“…UDP-glu-cose ceramide glucosyltransferase (UGCG) can reduce ceramide levels in vivo and induce cells to escape ceramide-induced apoptosis. [ 48 ] UGCG gene can regulate apoptosis-related pathways. Increased expression of UGCG can induce increased expression of anti-apoptotic gene Bcl-2, decreased expression of Bax and Caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…In our cell models, the globo pathway is prevalent; and we indeed find that GOLPH3 induces growth through effects on the globo series GSLs. Although the precise mechanism by which they exert their effects remains to be determined, Gb3 and the downstream metabolites Gb4, and sialo-Gb5 have been shown to cluster in GSL rich domains at focal adhesions (Steelant et al, 2002), where they bind to and activate integrins and RTK receptors to promote PI3K-Akt-mTOR signaling (Chuang et al, 2019;Furukawa et al, 2019;Hakomori Si, 2002;Park et al, 2012;Steelant et al, 2002;Wegner et al, 2018). An additional contributing factor to the pro-growth effects of GOLPH3 that is independent of GSL pathway being affected, is the decrease of Cer, a characterized tumor suppressor and inhibitor of cell proliferation (Hannun and Obeid, 2008;Reynolds et al, 2004).…”
Section: Discussionmentioning
confidence: 99%